Synergetic phenomenon between structural distortion and cobalt valence state and its effect on the oxygen evolution reaction in cobalt ferrites - Praxedes, Fabiano R. [UNESP]; Silva, Thayse R.; Ferreira, Maria C.M. [UNESP]; Nobre, Marcos A.L. [UNESP]; Macedo, Daniel A.; Lanfredi, Silvania [UNESP] (Elsevier, 2025)
Nanopowders of cobalt ferrite with the stoichiometry CoxFe3-xO4 (0.4 ≤ x ≤ 1.2) were synthesized at 80 °C using a co-precipitation method. The resulting crystalline, single-phase powders were characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), Fourier transform infrared spectroscopy (FTIR), and X-ray diffraction (XRD). Morphological analysis of the cobalt ferrite nanoparticles revealed the formation of spherical particle agglomerates at the nanoscale. Chemical bond analysis by infrared spectroscopy, based on the deconvolution of absorption bands, together with structural characterization by XRD and Rietveld refinement, confirmed the formation of a spinel-type phase with cubic symmetry and space group Fd-3m. The improved electrocatalytic performance was observed for the sample with the highest Co content (Co1.2Fe1.8O4, requiring 320 mV to achieve 10 mA cm−2). The structure-activity relationships indicate the OER mechanism in our cobalt ferrites is governed by three interconnected factors: octahedral Co3+ dominance, bond-angle flexibility, and increased Co content, synergistically enhancing catalytic efficiency.